Memaksimalkan Sosial Media Dalam Meningkatkan Penjualan Produk Home Industri - Luh Gede Putri Kusuma Pekerti (Parta: Jurnal Pengabdian Kepada Masyarakat, 2022)
Kukuh Village is one of the villages located in Kerambitan District, Tabanan Regency, Bali. One of the home industry entrepreneurs in Kukuh Village is now using banana tree midrib which can be processed as a snack for banana stem chips. Banana stem chips are one of the unique snacks known in Bali as Gedebong Chips. The home industry players who make banana midrib chips have difficulty in marketing the products they produce, so that not many people know about this  banana stem chips. Social media is one of the tools used in marketing products digitally to increase sales. Whether it's through social media Instagram, facebook, whatsapp, tik tok and other social media. The method of implementing this activity provides counseling and direct practice to home industry business actors regarding how to use social media and how to market products. This community service aims to maximize the use of social media in increasing sales of home industry products for banana stem chips.